Factors Associated With The Performance Of Family Planning Field Officers In Providing Kb Services In Samosir District Year 2023 - Manik, Desta Minarma (TOUR HEALTH JOURNAL, 2023)
Background: One of the efforts to create a quality family is through the Family Planning (KB) programme. Family Planning Field Officers (PLKB) are district / city government employees in the village / kelurahan in charge of implementing / managing, mobilising, empowering and mobilising and developing partnerships with various parties in the implementation of family planning service programmes. Purpose: The purpose of this study was to determine the factors related to the performance of PLKB. Method: The research method used descriptive analytic with cross sectional approach. Data collection was done by using questionnaire. Subjects were 34 respondents and analysed using Chi Square test. Results: The results of univariate analysis showed that the majority of respondents aged 38 - 48 years were 19 respondents, the majority of high motivation were 24 respondents, the majority of good leadership were 21 respondents and the majority of good performance were 29 respondents. The results of bivariate analysis showed that none of the 3 variables studied had a relationship with PLKB performance, namely age p=0.370, motivation p=0.104 and leadership p=0.278. Disscusion and Conclusion: The Department of Women's Empowerment and Child Protection as well as Population Control and Family Planning (DP3APPKB) Kab. Samosir should continue to improve PLKB knowledge through training, seminars, further education and others.